Comparison Between Advertising On Television And Social Media Toward Purchase Intention - Dianlestari, Cattleya; Hudrasyah, Herry (Journal of Business and Management, 2016)
Abstract. In this new era, there has been a shift on media. Social media is the new media which growing rapidly, and it used as media advertising. Now, people spent more time with social media than watching television. This study was the comparison of consumer response to advertising on television and social media to purchase intention. This result can be used to maximize the advertising medium that will be used by a company in this era that have been developed. This study uses a variable of the previous research framework that examines the relationship between advertising to the consumer purchase intention through attitude. Researchers using an experimental study to compare the response of the respondent. The researcher want to compare the advertising on television and social media to purchase intention. The study was conducted on three generations X , Y , and Z. Each generation is represented by five people. It is intended that each generation has its representatives. Data will be processed using statistical analysis Independent T-test and paired T-test. The results of this study indicate there is a differences between consumer response to purchase intention on advertising in media television and social media. Respondent more interested with advertising on social media than television.Keywords: Advertising on televison, advertising on internet or social media, consumer attitude, purchase intention.